Uterus didelphys with a successful term pregnancy - Anand, Smriti; Dhaiya, Soniya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Mullerian duct anomalies are congenital defects of female genital system that arise from abnormal embryological development of mullerianducts. Uterusdidelphys also known as double uterus is one of the least mulleriananomalies. Here we present a case of a woman with uterus didelphys and her successful full pregnancy. Patient came to our hospital with diagnosis of G1P0L0 with 39 weeks with antepartum hemorrhage with active bleeding. On ultrasound she was found to be type iv placenta previa, in view of same we had done her lower segment cesarean section with delivery of a 2.5 kg female baby with intraoperative findings of two uterus and two cervix i.e uterus didelphys in which pregnancy was present in right uterus, placenta covering os. Post operative period was uneventful. Patient who have uterus didelphys due to mullerian defect not associated with difficulty in conception but there is increase incidence of preterm labour, malpresentation and malposition. Howeverwith appropriate antenatal and intrapartum surveillance pregnancy outcome are good.